The development of a pre-registration nursing competencies assessment tool for use across Australian universities : final report. - Crookes, Patrick; Brown, Roy (Australian Learning and Teaching Council, 2010)
Debate about the lack of consistency in the competency of nursing graduates has gained momentum in recent years. In part, this stems from disparities in clinical assessment tools in use across Australia's 39 nursing schools to evaluate graduates' readiness for nurse registration. But it has also thrown up issues around the nursing profession's expectations of new graduates and how prepared they are for practice. The following report is the culmination of a project to address some of these issues by developing a new nationally agreed competency assessment tool for nursing graduates. The tool applies to Australian universities with nursing programs that lead to eligibility for nurse registration in all states and territories. [Executive summary]